2012
DOI: 10.1111/j.1423-0410.2012.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of roledumab, a novel human recombinant monoclonal anti‐RhD antibody with an optimized Fc for improved engagement of FCγRIII, in healthy volunteers

Abstract: Background and Objectives A human recombinant monoclonal anti-RhD IgG may be useful to prevent RhD allo-immunization. Roledumab is such an antibody with a glycosylation pattern optimized for biological activity. The objective of the study was to assess the safety and pharmacokinetics of roledumab in healthy RhD-negative volunteers.Materials and Methods A total of 46 subjects received doses of 30-3000 lg i.v. of roledumab or placebo using a double-blind escalating single-dose design; 12 of these subjects also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This property is related to the lower expression of the Fut8 gene in rat myeloma YB2/0 cells compared with other commonly used cell lines, such as CHO cells [30]. Two EMABling ® MAbs, the anti-RhD roledumab [41] and the anti-CD20 ublituximab [42], are currently in clinical development. Moreover, we [29, 41] and other groups [4345] have demonstrated that such improved effector functions are associated with higher therapeutic efficacy in humans, especially in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…This property is related to the lower expression of the Fut8 gene in rat myeloma YB2/0 cells compared with other commonly used cell lines, such as CHO cells [30]. Two EMABling ® MAbs, the anti-RhD roledumab [41] and the anti-CD20 ublituximab [42], are currently in clinical development. Moreover, we [29, 41] and other groups [4345] have demonstrated that such improved effector functions are associated with higher therapeutic efficacy in humans, especially in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of core fucosylation of the IgG Fc has mainly received attention because of the possibilities to produce more efficacious therapeutic antibodies, and glycoengineered cancer antibodies carrying afucosylated Fc glycans are currently in clinical development (reviewed by Yamane‐Ohnuki and Satoh) . For this reason, Beliard and colleagues selected, in their search toward a recombinant anti‐D to replace plasma‐derived RhIG, a monoclonal anti‐D (LFB‐R297) that contains an optimized glycosylation profile characterized by a low fucose content . Since there is only little variation in the fucose content of human IgG found in serum, and on the glycopeptide level on average 93% of IgG do contain core fucose, the relevance of the fucose content of polyclonal RhIG has never been studied.…”
mentioning
confidence: 99%
“…11 For this reason, Beliard and colleagues 5 selected, in their search toward a recombinant anti-D to replace plasma-derived RhIG, a monoclonal anti-D (LFB-R297) that contains an optimized glycosylation profile characterized by a low fucose content. 12 Since there is only little variation in the fucose content of human IgG found in serum, and on the glycopeptide level on average 93% of IgG do contain core fucose, the relevance of the fucose content of polyclonal RhIG has never been studied. However, recently, we observed a low Fc-fucosylation (down to approx.…”
mentioning
confidence: 99%
“…Anti‐D immunoglobulin is currently derived from human plasma of immunised, boosted donors. Monoclonal anti‐D is not available as a substitute and recombinant anti‐D was ineffective in several trials (Kumpel, ), although development and glycosylation research is ongoing (Olovnikova et al , ; Yver et al , ).…”
Section: Discussionmentioning
confidence: 99%